Helicobacter pylori in Human Stomach: The Inconsistencies in Clinical Outcomes and the Probable Causes - Alexander, Sneha Mary; Retnakumar, Radhakrishnan Jayalakshmi; Chouhan, Deepak; Devi, Thillai Natarajan Barani; Dharmaseelan, Sanjai; Devadas, Krishnadas; Thapa, Namrata; Tamang, Jyoti Prakash; Lamtha, Sangey Chhophel; Chattopadhyay, Santanu (Frontiers in Microbiology, 2021)
Pathogenic potentials of the gastric pathogen, Helicobacter pylori, have been proposed, evaluated and confirmed by many laboratories for nearly four decades since its serendipitous discovery in 1983 by Barry James Marshall and John Robin Warren. H. pylori is the first bacterium to be categorized as a definite carcinogen by the International Agency for Research on Cancer (IARC) of the World Health Organization (WHO). Half of the world’s population carries H. pylori, which may be responsible for severe gastric diseases like peptic ulcer and gastric cancer. These two gastric diseases take more than a million lives every year. However, the role of H. pylori as sole pathogen in gastric diseases is heavily debated and remained controversial. It is still not convincingly understood, why most (80-90%) H. pylori infected individuals remain asymptomatic, while some (10-20%) develop such severe gastric diseases. Moreover, several reports indicated that colonization of H. pylori has positive and negative associations with several other gastrointestinal (GI) and non-GI diseases. In this review we have discussed the state of the art knowledge on ‘H. pylori factors’ and several ‘other factors’, which have been claimed to have links with severe gastric and duodenal diseases. We conclude that H. pylori infection alone does not satisfy the ‘necessary and sufficient’ condition for developing aggressive clinical outcomes. Rather, the cumulative effect of a number of factors like the virulence proteins of H. pylori, local geography and climate, genetic background and immunity of the host, gastric and intestinal microbiota, dietary habit and history of medicine usage together determine whether the H. pylori infected person will remain asymptomatic or will develop one of the severe gastric diseases.